2002
DOI: 10.1046/j.1365-2427.2002.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of piscivore‐mediated habitat use on growth, diet and zooplankton consumption of roach: an individual‐based modelling approach

Abstract: SUMMARY 1. We used an individual based modelling approach for roach to (i) simulate observed diel habitat shifts between the pelagic and littoral zone of a mesotrophic lake; (ii) analyse the relevance of these habitat shifts for the diet, activity costs and growth of roach; and (iii) quantify the effects of a hypothetical piscivore‐mediated (presence of pikeperch) confinement of roach to the littoral zone on roach diet, activity costs and growth. 2. The model suggests that in the presence of pikeperch, roach s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 44 publications
3
40
1
Order By: Relevance
“…The diet of roach in Lago Maggiore seems rather similar to that reported in the literature (Niederholzer & Hofer 1980;Rask 1989;Horppila 1998;Lappalainen et al 2001;Guthruf 2002), but the roach in this study did not eat macrophytes, unlike in other lacustrine environments (Niederholzer & Hofer 1980;Horppila 1998;Guhtruf 2002;Hölker et al 2002). This may be due to the low abundance of aquatic plants in Lago Maggiore caused by low nutrient concentration of the lake, fluctuating water levels and the steep littoral zone as found by Niederholzer & Hofer (1980) in a Tyrolese lake and by Garcia-Berthou (1999) in the Banyoles Reservoir.…”
Section: Discussionsupporting
confidence: 86%
“…The diet of roach in Lago Maggiore seems rather similar to that reported in the literature (Niederholzer & Hofer 1980;Rask 1989;Horppila 1998;Lappalainen et al 2001;Guthruf 2002), but the roach in this study did not eat macrophytes, unlike in other lacustrine environments (Niederholzer & Hofer 1980;Horppila 1998;Guhtruf 2002;Hölker et al 2002). This may be due to the low abundance of aquatic plants in Lago Maggiore caused by low nutrient concentration of the lake, fluctuating water levels and the steep littoral zone as found by Niederholzer & Hofer (1980) in a Tyrolese lake and by Garcia-Berthou (1999) in the Banyoles Reservoir.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, nine detailed acoustic surveys did not provide a clear pattern between day and night results, meaning some other factors that were not monitored were important. Possible explanations include presence or absence of fish predators (Schulze et al 2006;Hölker et al 2007;Horký et al 2008), seasonal affects on distributions (Borcherding et al 2002;Jacobsen et al 2004;Yule et al 2009), age composition and habitat preferences (Schulze et al 2006;Dörner et al 2007;Prchalová et al 2008), moon phase (Gaudreau and Boisclair 2000;Horký et al 2006) and food supply (Hölker et al 2002;Wojtal et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It may feed mostly on macrophytes in Lake Annecy to avoid potential predators, which explains the large proportion of Chara in roach intestine. Holker et al (2002) and Sharma and Borgstrom (2008) suggested that roach shifts from a zooplankton diet to less nutritious macrophytes and filamentous algae to avoid predators, but δ 13 C signature of roach was quite low compared to Chara. Mostly the submerged macrophytes in lakes have very high carbon isotopic signatures as compare to consumers (Syvaranta et al 2006), which we found to be true in Lake Annecy.…”
Section: Discussionmentioning
confidence: 99%